Prevalence of Three-Rooted Deciduous Mandibular Molars in the Children of Northwestern Iran - Maryam Khosrozadeh (Hindawi Limited, 2021)
Introduction. Although primary teeth have a determinative role in development of normal occlusion, few studies about anomalies related to deciduous dentition have been conducted so far. Regarding recent improvements in common knowledge and the importance of maintaining primary teeth until eruption of succedaneous teeth, identifying the morphology of primary teeth and probable variations is of great importance to achieve optimal therapeutic outcome. This study aims to determine the prevalence of three-rooted mandibular primary molars in a population of northwestern Iran. Materials and Methods. In this descriptive cross-sectional study, periapical radiographs of patients attending private oral and maxillofacial radiology offices in the northwestern region of Iran from 2017 to 2019 were retrospectively reviewed. A total of 300 cases in the 3–10-year age range having bilateral periapical radiographs from mandibular primary molars were screened. First and second primary molars were observed meticulously. Gender, side of the mandible (right or left), symmetry, overall prevalence, and prevalence considering the type of molar (D or E) were recorded and analyzed. Results. Overall prevalence of three-rooted mandibular primary molars was 9.33% ( 28/300), 92.9% of which were unilateral. The prevalence of teeth showing supernumerary roots among all teeth examined was 2.5% (30/1200). Considering symmetry and gender, the occurrence of these three-rooted primary molars did not differ significantly (respectively, p=0.832 and p=0.541). However, there was a significant relationship between the occurrence of supernumerary roots and left side for three-rooted first molars and right side for three-rooted second molars (p=0.021). Conclusion. Obtained data show that three-rooted mandibular primary molars in children of northwest region of Iran have a prevalence of approximately 10 % which urges some specific considerations in exodontic and endodontic procedures.